Biotransformation of biphenyl by the filamentous fungus Talaromyces helicus - Romero, María Cristina (2005)
The filamentous fungus Talaromyces helicus, isolated from oil-contaminated sludge, oxidizes biphenyl via 4-hydroxybiphenyl to the dihydroxylated derivatives 4,4′-dihydroxybiphenyl and 3,4-dihydroxybiphenyl, which, to a certain extent, are converted to glycosyl conjugates. The sugar moiety of the conjugate formed from 4,4′-dihydroxybiphenyl was identified as glucose. Further metabolites: 2-hydroxybiphenyl, 2,5-dihydroxylated biphenyl, and the ring cleavage product 4-phenyl-2-pyrone-6-carboxylic acid accumulated only in traces. From these results the main pathway for biotransformation of biphenyl in T. helicus could be proposed to be the excretion of dihydroxylated derivatives (>75%) and their glucosyl conjugates (<25%).